Exploring longitudinal changes in lexical and syntactic features in beginning-level EFL learner writing. (December 2021) - Kim, Minkyung
Abstract: This study examined longitudinal changes in lexical and syntactic features in the writing of beginning-level learners in an English as a foreign language (EFL) context. Writing samples were produced by 90 Korean EFL undergraduate students, each of whom produced seven essays over an academic semester, totaling 630 essays. Lexical complexity was measured by lexical density, variation, and sophistication. Syntactic complexity was measured by global complexity, subordination, coordination, and noun phrase complexity. The findings indicate that over time, beginning-level learners showed developmental patterns in lexical features, such that they tended to produce more sophisticated content words and use more function words (e.g., pronouns and articles), which may be difficult for beginning-level learners to learn and use. The findings also indicate that lexical features progressed to a larger degree than syntactic features in beginning-level learners' writing. In addition, competitive relationships were found between phrasal-level and clause-level complexity and between the use of function words and complex nominals. Last, the use of function words and complex nominals were interrelated, which indicates that changes in lexical and syntactic features appear to be interwoven, thus highlighting the importance of jointly accounting for lexical and syntactic features. Highlights: Lexical and syntactic changes in beginning-level EFL writing were explored. Beginning-level EFL learners showed developmental patterns in lexical features. Lexical features progressed to a larger degree than syntactic features. The importance of considering both lexical and syntactic features is highlighted.